Implementation of Regulation of the Minister of Health Number 10 of 2021 in Giving Vaccines (Study at Bhayangkara Hospital Bengkulu) - Bernat Siregar; Budiman Sakti; Edi Darmawi; Heru Purnawan; Harmiati Harmiati (Journal of Social Science and Humanities, 2022)
The purpose of this study was (1) to find out the implementation of the Minister of Health Regulation Number 10 of 2021 in the Provision of COVID-19 Vaccines at the Bhayangkara Bengkulu Hospital and (2) to find out the obstacles in the process of administering the COVID-19 vaccine at the Bhayangkara Bengkulu Hospital. This study uses a qualitative approach using descriptive methods. Collecting data in the form of primary data and secondary data. There were 5 informants in this study consisting of 1 person in charge of vaccination, 1 coordinator of the vaccination team, 1 health worker and 2 people receiving vaccines. The results showed that the implementation of the Minister of Health Regulation Number 10 of 2021 in Vaccination at Bhayangkara Hospital Bengkulu on reducing the growth rate of COVID-19 cases was quite influential according to what residents and related parties felt in terms of the four-variable approach proposed by Edward III in Agustino (2016), namely communication, resources, disposition, and bureaucratic structure, it can be concluded that the policies taken are quite appropriate although there are still some obstacles in the implementation of the COVID-19 Vaccination.